Parental support and coach influence towards career decision making self-efficacy among national student athletes in Malaysia - Retnam, Elaiyaraj; Asmuni, Azizan; Hamzah, Siti Raba'ah (Human Resource Management Academic Research Society, 2018)
The purpose of this study is to understand the factors influencing career decision making self-efficacy among student athletes in National Sports Schools in Malaysia. This is a descriptive and correlative research study and based on theoretical framework of Social Cognitive Career Theory (Lent, Brown, & Hackett, 1996). This study focused on the national athletes who are currently studying Pre-University in the National Sports Schools. By using random sampling technique, 145 respondents among student athletes from two National Sports School were selected. Data were collected using the drop and pick-up method and self-administered questionnaires survey method. The analysis showed that most of the athletes demonstrated a moderate career decision making self-efficacy. Besides that, results from the correlation analysis indicate parental support and coach influence have significantly positive relationship with career decision making self-efficacy at 0.05 level of significant. While the test for regression analysis shows that both independent variables, explained 51.0% variance in student athletes career decision making self-efficacy. From the two predictors, parental support was the dominant predictor in student athletes career decision making self-efficacy with (Beta = 0.573) followed by coach influence (Beta= 0.218). These two predictors; parental support and coach influence are important and crucial in order to inculcate the career decision making self-efficacy of national student athletes. By emphasizing on the career development of national student athletes, athletes could easily boost their confidence and knowledge about career needs and have a secured future upon retiring as an athlete.